Autoregulation by "repetitions in reserve" leads to greater improvements in strength over a 12-week training program than fixed loading - Graham, T.; Cleather, D. J. (The Journal of Strength and Conditioning Research, 2021)
Autoregulated (AR) training involves altering resistance session parameters based on the athlete's readiness to train. One potential benefit of AR training may be that training intensity can reflect an athlete's increasing strength level throughout a training program and can be contrasted with fixed loading (FL) where the load is stipulated at the start of the program. In this study, 31 resistance-trained men participated twice weekly in an AR or a FL squat program. For the FL group, the load was prescribed as a percentage of the pre-test 1-repetition maximum, whereas for the AR group, the load was prescribed based on the number of "repetitions in reserve," such that the intensities were theoretically the same (volume was also matched). Both groups showed a significant increase in front squat (FS) and back squat (BS) performance, but the magnitude of this was significantly greater for the AR program (FS: AR +11.7%, FL +8.3%, p = 0.004, Eta2p = 0.255; BS: AR +10.8%, FL +7.1%, p = 0.006, Eta2p = 0.233). The AR group was trained at a greater intensity (average weekly intensity; FS: AR 83.2 ± 13.3%, FL 80.4 ± 10.0%, p < 0.001, Eta2p = 0.240; BS: AR 83.6 ± 12.7%, FL 80.4 ± 10.0%, p = 0.006, Eta2p = 0.159). The results of this study support the contention that AR can be used to accommodate the increasing strength level of the athlete during the course of a program and that such a strategy is effective in eliciting greater strength adaptations across 12 weeks.